Identification and validation of human papillomavirus encoded microRNAs. - Kui Qian; Tuuli Pietilä; Mikko Rönty; Frederic Michon; Mikko J Frilander; Jarmo Ritari; Jussi Tarkkanen; Lars Paulín; Petri Auvinen; Eeva Auvinen (PLoS ONE, 2013)
We report here identification and validation of the first papillomavirus encoded microRNAs expressed in human cervical lesions and cell lines. We established small RNA libraries from ten human papillomavirus associated cervical lesions including cancer and two human papillomavirus harboring cell lines. These libraries were sequenced using SOLiD 4 technology. We used the sequencing data to predict putative viral microRNAs and discovered nine putative papillomavirus encoded microRNAs. Validation was performed for five candidates, four of which were successfully validated by qPCR from cervical tissue samples and cell lines: two were encoded by HPV 16, one by HPV 38 and one by HPV 68. The expression of HPV 16 microRNAs was further confirmed by in situ hybridization, and colocalization with p16INK4A was established. Prediction of cellular target genes of HPV 16 encoded microRNAs suggests that they may play a role in cell cycle, immune functions, cell adhesion and migration, development, and cancer. Two putative viral target sites for the two validated HPV 16 miRNAs were mapped to the E5 gene, one in the E1 gene, two in the L1 gene and one in the LCR region. This is the first report to show that papillomaviruses encode their own microRNA species. Importantly, microRNAs were found in libraries established from human cervical disease and carcinoma cell lines, and their expression was confirmed in additional tissue samples. To our knowledge, this is also the first paper to use in situ hybridization to show the expression of a viral microRNA in human tissue.